2018
DOI: 10.21303/2504-5679.2018.00585
|View full text |Cite
|
Sign up to set email alerts
|

Research of Certain Pathogenic Characteristics of Clinical Isolates of Staphylococci of Skin Biome

Abstract: A serious problem in patients with atopic dermatitis (AD) is the frequent attachment of a secondary skin infection. Among the microbes colonizing the skin of patients suffering from AD, S. aureus takes the lead. According to different authors, from the skin of 80–95 % of patients are sown Staphylococcus aureus. The survival of bacteria in a biotope is promoted by the persistent properties of microorganisms. Aim of the research: to determine the adhesive properties and antilysozyme activity of clinical strains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 8 publications
(7 reference statements)
0
2
0
Order By: Relevance
“…8, tracks No. [1][2][3][4][5][6][7][8][9][10][11][12], the number of obtained fragments ranged from 6 to 11. The degree of affinity between isolates obtained from intact skin ranged from 70.6 % to 88.9 % (mean 80.8±2.1 %).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8, tracks No. [1][2][3][4][5][6][7][8][9][10][11][12], the number of obtained fragments ranged from 6 to 11. The degree of affinity between isolates obtained from intact skin ranged from 70.6 % to 88.9 % (mean 80.8±2.1 %).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown differences in a number of phenotypic traits of S. aureus strains that colonize the affected and intact areas of the skin of patients with allergodermatoses [5][6][7]. In this case, the density of skin colonization of patients in the locus morbi directly correlates with the severity of these diseases.…”
Section: Introductionmentioning
confidence: 99%